Regional Economic Issues, April 2015, Europe : The Western Balkans: 15 Years of Economic Transition. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2015)
This report analyses the main economic developments and achievements in the Western Balkan countries, and lays out the key macroeconomic policy challenges for the future.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet